AMERICAN CULTURAL VALUES AS REFLECTED IN THE CHARACTER OF BRAD COHEN IN PETER WERNER’S MOVIE FRONT OF THE CLASS - Widianingsih, Karomah (LANTERN (Journal on English Language, Culture and Literature), 2016)
This study focuses on American cultural values reflected by Brad Cohen in Front of the Class Peter Werner’s movie. Front of the Class movie describes some reflections of American cultural values depicted by the main character named Brad Cohen. The aims of this study are to describe the intrinsic and extrinsic aspects of the movie. The writer employs library research to support the data analysis derived from some references such as some related books, journals, articles, and encyclopedias. To analyze the intrinsic aspects, the writer uses some theories of narrative elements and cinematographic elements. To analyze the extrinsic aspects, the writer applies theory of personal and cultural values by Roy D’Andrade. Furthermore, the writer also involves some aspects of cultural values from Shalom H Schwartz’s theory. The result of this study shows that, based on Roy D’Andrade’s theory, the main character of the movie, Brad Cohen has applied individualism, altruism, and industry value aspects. In addition, the writer finds some similar American cultural values items of Roy D’Andrade’s theory and Shalom H. Schwartz’s theory. Those items are choosing my own goal, being creative, treating people equally, being honest, enjoying life, and pursuing knowledge.